Ulos Ragi Pakko and Batak Toba Cultural Meaning in a North Sumatra Museum Collection - Desi Herawati; Muaz Tanjung (Yupa: Historical Studies Journal, 2026)
This study examines Ulos Ragi Pakko as a Batak Toba cultural artifact preserved in the collection of the North Sumatra Provincial State Museum. It is motivated by the need to document and interpret traditional textiles as material representations of Batak identity, social values, and historical continuity amid contemporary cultural change. The study asks how Ulos Ragi Pakko functions as a cultural artifact and what symbolic meanings it embodies in Batak Toba society. Using a qualitative historical approach, data were collected through artifact observation, museum documentation, literature review, and contextual interpretation of cultural sources related to Batak traditions. The findings show that Ulos Ragi Pakko is not only a traditional woven textile but also a medium of social communication that reflects kinship structures, customary values, ceremonial functions, and the cultural worldview of the Batak Toba people. The artifact embodies meanings associated with respect, social status, solidarity, and cultural continuity across generations. The study contributes to cultural history and museological studies by showing how museum collections interpret, represent, and transmit cultural meanings to wider audiences.